2013
DOI: 10.1007/s12544-013-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Airline Facebook pages – a content analysis

Abstract: Purpose The emergence of new media has changed the way how airlines interact with the public. This study analyzes how airlines use one of the most popular new media platforms, Facebook, to manage public relations, communicate with customers and diversify their sales channels. This topic has not been covered by scientific literature so far. Methods This paper uses content analysis to identify types of content provided by airlines on their official Facebook pages and extent of services offered (customer service,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Brand posts constitute an important component of airlines' social media activities (Grančay, ), and “ fan engagement ” is an important attribute of airlines' social media usage (see, e.g., Parveen et al, ). Travelers who are fans of an airline can see brand posts and engage with them by liking, commenting, and sharing.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Brand posts constitute an important component of airlines' social media activities (Grančay, ), and “ fan engagement ” is an important attribute of airlines' social media usage (see, e.g., Parveen et al, ). Travelers who are fans of an airline can see brand posts and engage with them by liking, commenting, and sharing.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%
“…We contribute to that literature but focus more on the strategy and tactics of the marketing firm itself, as an important gap in the literature. The aviation industry was chosen because firms of this sector adopt an active approach to social media marketing, many of which have large fan bases following their brand messages on social media (Grančay, ). We study engagement to a greater extent than previous studies of the airline sector.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of Facebook of airlines using content analysis was done by Grancay (2014). The findings revealed that Airline FB pages contained only limited information and are not substitutes for airline websites.…”
Section: Airlines Companies Facebookmentioning
confidence: 99%